Comparative Effects of Percussion Theragun Versus Physical Activity in Non-Specific Neck Pain in Young Adults – A Randomized Clinical Tr - Reshi, Chockalingam; Senthil, Kumar; Pranata Dalal, Inamdar (INTI International University, 2023)
Background: The percussion theragun uses fast oscillatory back and forth movements to produce vibrations of different frequencies. Handheld percussive massage treatment has acquired fame as of late, for both remedial use and in sports practice. Physical activity is any movement that uses energy that improves strength, flexibility. With both the possible treatment options, the study raises the question of which of the two produces better results in subjects with Non-specific neck pain in terms of reduction of pain and increase in range. The objective of this study was to assess and compare the therapeutic effects of the percussion theragun with physical activity for the treatment of non-specific neck pain. Method and Measures: The study was conducted on 36 subjects with non-specific neck pain who were given 3 consecutive sessions (in a span of 3 days) of intervention. Through randomized method subjects were divided into the percussion theragun group (group A) and conventional physical activity group (group B). Outcome measures such as VAS (visual analogue scale) and Neck range of motion were assessed Results: The nonspecific neck pain participants in Group A and Group B showed significant improvement in extension, right lateral flexion, left lateral flexion neck ROM and reduction in VAS after exposed to the respective intervention. However, the Group A showed a significant improvement in VAS and ROM when compared with Group B. Conclusion: The current study provided the evidence to prove that the protocols used in this study show significant reduction in pain and range of motion in subjects with non-specific neck pain in both the groups. The percussion theragun group showed significantly greater improvement than the physical activity group.